UJI ANTAGONISME Trichoderma spp. TERHADAP Phytophthora palmivora PENYEBAB PENYAKIT GUGUR BUAH KELAPA - Ryan A. Kaunang; Berty H. Assa; Vivi B. Montong (COCOS, 2018)
ABSTRACT  The deciduous fall of coconut fruit is caused by Phytophthora palmivora fungus.  This study aims to determine the ability of Trichoderma spp. Inhibiting P. palmivora on PDA media in vitro.  Research method used experimentally, that is antagonism test with method of dual culture method. P. palmivora in isolation from coconut fruit showing symptoms of the disease. The results showed that the antagonistic fungus Trichoderma spp could suppress the growth and development of the P. palmivora fungus, the average percentage of inhibition of the antagonistic fungus Trichoderma spp. of the pathogenic fungi of P. palmivora in vitro on PDA media on the fifth day is (100%) for simultaneously inoculated antagonism test and (40,62%) for antagonism test wherein antagonistic inoculation 4 days after pathogen. On the seventh day, the average percentage of inhibition of the antagonistic fungus Trichoderma spp. of the pathogenic fungus P. palmivora is (100%) for both treatments of this antagonism test.  Key Words: Coconut Nut Fall, Phytophthora palmivora, Antagonist